INTEGRASI KARAKTER DAN LITERASI SAINS DALAM PEMBELAJARAN IPA SEBAGAI UPAYA PENINGKATAN HASIL BELAJAR SISWA KELAS VII SMP NEGERI 17 PEKANBARU - Ernawati, Ernawati; Suryawati, Evi; Suzanti, Fitra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Classroom Action Research has been conducted consisting of two cycles. This study aims to improve the learning outcomes of science students of class VII SMP Negeri 17 Pekanbaru with the integration of character and science literacy in science learning. Research starts from the planning stage, the implementation of the action, the observation stage and the last was done reflection to analyze the deficiencies that occur in the learning activities in order to improve the learning activities in the next cycle. This research was conducted from March to May 2018. The subjects of this study were the students of class VII1 semester of which amounted to 40 students, consisting of 18 male students and 22 female students. Parameters in the study were student learning outcomes consisting of affective apsek, psikomotor and cognitive aspects that consist of students' absorption and mastery of student learning. The results showed the students' learning outcomes increased. On the affective aspect increased from 3.01 (B) in cycle I to 3.08 (B) in cycle II. Psychomotor aspect increased from 78.70 (C) in cycle I to 84.58 with (C) in cycle II. The average score of cognitive aspects of students is 79.87 (C) in cycle I and increased to 81.02 (C) in cycle II. Student learning mastery in cycle I is 72.5% and increased to 85% in cycle II. Based on the results of research, it can be concluded that by integrating the character and science literacy in science learning can improve student learning outcomes of class VII1 SMP Negeri 17 Pekanbaru.Key Words : Character, Science Literacy, Learning Outcomes